2021
DOI: 10.1371/journal.pone.0248885
|View full text |Cite
|
Sign up to set email alerts
|

A faster and less costly alternative for RNA extraction of SARS-CoV-2 using proteinase k treatment followed by thermal shock

Abstract: One of the biggest challenges during the pandemic has been obtaining and maintaining critical material to conduct the increasing demand for molecular tests. Sometimes, the lack of suppliers and the global shortage of these reagents, a consequence of the high demand, make it difficult to detect and diagnose patients with suspected SARS-CoV-2 infection, negatively impacting the control of virus spread. Many alternatives have enabled the continuous processing of samples and have presented a decrease in time and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Here, we report continuous genomic surveillance at the Benin reference laboratory on samples obtained from 4 sites in southern Benin during late April–mid-July 2021 ( Figure 1 , panel A). During the study period, routine testing at the reference laboratory and associated satellite laboratories in Benin averaged at 1,370 samples per day ( Figure 1 , panel B), a 900% increase from a comparable timeframe in 2020 ( 6 ) ( Figure 1 , panel B). The decentralization of diagnostic testing and simplification of extraction protocol contributed to increased testing ( 7 ).…”
Section: The Studymentioning
confidence: 99%
“…Here, we report continuous genomic surveillance at the Benin reference laboratory on samples obtained from 4 sites in southern Benin during late April–mid-July 2021 ( Figure 1 , panel A). During the study period, routine testing at the reference laboratory and associated satellite laboratories in Benin averaged at 1,370 samples per day ( Figure 1 , panel B), a 900% increase from a comparable timeframe in 2020 ( 6 ) ( Figure 1 , panel B). The decentralization of diagnostic testing and simplification of extraction protocol contributed to increased testing ( 7 ).…”
Section: The Studymentioning
confidence: 99%
“…Others found a proteinase K digest prior to heat lysis to be beneficial to detecting SARS-CoV-2 in patient samples [ 15 , 16 ]. In our hands, heat lysis of SARS-CoV-2 VPM gave significantly worse results than using a lysis buffer; therefore, that avenue was not pursued further for in vitro samples.…”
Section: Discussionmentioning
confidence: 99%
“…For SARS-CoV-2, several groups have developed direct RT-qPCR methods for detection aimed at patient swabs. The most commonly used method is direct use of swabs following a heating step: 30 min at 65 • C or increasingly shorter periods up to 95 • C. With or without addition of commercial buffers or detergents, a Ct difference between four and seven cycles was observed compared with extracted vRNA [8][9][10][11][12][13][14][15][16]. Other methods include the addition of proteinase K to patient swab samples, showing 4-6 cycle differences, but no proof of virus inactivation was shown for these samples [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…FDA and other authors have reported the optimal human endogenous genes in the SARS-CoV-2 RT-qPCR detection. The RNAse P and Glyceraldehyde-3-Phosphate Dehydrogenase (GAPDH) are among the genes that act as an excellent internal control by excluding the possibility of false results due to the presence of low quality and integrity of RNA samples [ 65–67 ].…”
Section: Influencing Factors On Sars-cov-2 Detectionmentioning
confidence: 99%